The Role of the Satintelkam State Security Unit in Early Detection of the Spread of Radicalism and Terrorist Groups in the Jurisdiction of the Blitar City Police (Advances in Police Science Research Journal, 2024)
Radicalism is an understanding and ideology that specifically wants to change the social and political conditions that exist in a country. The purpose of writing in this final project is to describe the initial role, influencing factors, and efforts made by the Satintelkam State Security Unit in early detection of the spread of radicalism and terrorist groups in the jurisdiction of the Blitar City Police Station. The conceptual literature of this research uses Management Theory (POAC and 4M), as well as Law As A Tool of Social Engineering Theory. While the concepts used include the Concept of Police Intelligence Unit, the Concept of Early Detection, the Concept of Radicalism, and the Concept of Terrorist Groups. The writing method used is a qualitative method with descriptive writing types and field studies. Data sources include primary and secondary through interviews and documentation studies. Data validity is obtained using data triangulation. The location of the study is the jurisdiction of the Blitar City Police in the East Java region. The jurisdiction of the Blitar City Police consists of 9 sub-districts with 6 sub-districts being the administrative region of Blitar Regency. The results showed that there are still obstacles in the implementation of early detection, especially in organizing. Which in the performance of their duties still overlaps in other warrants at the time of early detection. Factors that influence this are the lack of personnel, budgets that do not always meet needs, to incomplete facilities and infrastructure. The conclusion that can be taken is that the Blitar City Police Intelligence Unit has not played a maximum role, so it is necessary to add adequate personnel, improve the budget, and submit applications for new facilities and infrastructure.
Keywords: Kata Kunci : Peran, Deteksi Dini, Radikalisme, Kelompok Teroris